2000
DOI: 10.1023/a:1026552405042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin and Linolenic Acid on Mammary Cancer in Transgenic Mice with c-neu Breast Cancer Oncogene

Abstract: Breast cancer is one of the most common cancers and is a leading cause of mortality in women. The TG.NK transgenic mouse line expresses the c-neu breast cancer oncogene under the control of a MMTV promoter and appears to be a useful animal model for evaluation of intervention strategies to delay/prevent breast cancer. Fiber-rich nonpurified diet (NTP-2000) and some retinoid analogues have been shown to significantly delay the development of mammary cancer in the TG.NK model. Four-week-old hemizygous TG.NK fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 23 publications
2
21
0
2
Order By: Relevance
“…In agreement with these results, Rao et al (2000) reported that 4-HPR was unable to decrease the mammary tumor incidence and average tumor weight in transgenic mice bearing c-neu. However, Jinno et al (1999) reported that 4-HPR was able to induce apoptosis in the preneoplastic human mammary epithelial 184-B5/HER cell line bearing high levels of HER2/ neu.…”
Section: Discussionsupporting
confidence: 79%
“…In agreement with these results, Rao et al (2000) reported that 4-HPR was unable to decrease the mammary tumor incidence and average tumor weight in transgenic mice bearing c-neu. However, Jinno et al (1999) reported that 4-HPR was able to induce apoptosis in the preneoplastic human mammary epithelial 184-B5/HER cell line bearing high levels of HER2/ neu.…”
Section: Discussionsupporting
confidence: 79%
“…The treatment of these transgenic mice with melatonin significantly reduces the incidence of these mammary lesions, the expression of N-ras protein in focal hyperplasic lesions, and the incidence of adenocarcinomas (Mediavilla et al 1997). In transgenic mice expressing the c-neu breast cancer oncogene under the control of an MMTV promoter, melatonin delayed the appearance of palpable tumors and the growth of the tumors (Rao et al 2000).…”
Section: Evidence From In Vivo Studies On Animal Modelsmentioning
confidence: 99%
“…It has anticarcinogenic [Lissoni, 2000;Rao et al, 2000] and free radical scavenging [Qi et al, 2001;Wakatsuki et al, 2001] properties as well.…”
Section: Introductionmentioning
confidence: 99%